2019
DOI: 10.1016/j.sdentj.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Regional odontodysplasia: An analysis of 161 cases from 1953 to 2017

Abstract: Background and objectiveRegional odontodysplasia (RO) is a localized developmental anomaly involving both dentitions. The characteristic clinical findings are soft discolored several contiguous teeth with atypical morphology associated with swelling or abscess formation. Radiographic images of the involved teeth show a ghost-like appearance because enamel and dentin are hypoplastic and hypocalcified. Although RO is known for more than seven decades, the literature on RO is mostly limited to case reports.The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
16
2
Order By: Relevance
“…However, the collected data shows that there is no significant sex predilection of regional odontodysplasia. On the contrary, other literature gives ratios as high as 1.37:1, 1.4:1 and even 1.7:1 of female to male cases, which shows a big difference from our results presented in this review (1.03:1) [18][19][20]. The possible explanation for this disparity can be a high number of new case reports taken into account in this article compared to older works.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the collected data shows that there is no significant sex predilection of regional odontodysplasia. On the contrary, other literature gives ratios as high as 1.37:1, 1.4:1 and even 1.7:1 of female to male cases, which shows a big difference from our results presented in this review (1.03:1) [18][19][20]. The possible explanation for this disparity can be a high number of new case reports taken into account in this article compared to older works.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent systematic review of published RO cases by Nijakowski et al [4] reported no significant gender predilection. Conversely, other literature showed that women might be slightly more affected than men [3].…”
Section: Introductionmentioning
confidence: 79%
“…However, it was found that this anomaly has no ethnic tendency. The mandible is less frequently affected than the maxilla [1,3]. A recent systematic review of published RO cases by Nijakowski et al [4] reported no significant gender predilection.…”
Section: Introductionmentioning
confidence: 99%
“…It often occurs in children and adolescents and with a recorded peak at ages 2-5 and 8-12 years. In most cases, both dentitions are involved, and the maxilla is more commonly affected [20]. The ratio of males to females is reported to be 1:1.37 [2].…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%